Enlightenment Through Film: Why Has Bodhi-Dharma Left for the East? - Avila, Wanda E. (The journal of religion and film, 2010)
Through its mandala-like structure, Why Has Bodhi-Dharma Left for the East? (Korea, 2007) provides a kind of Enlightenment experience to the spectator. Like the mandala, Bodhi-Dharma has a symbol of the Truth at its center. Around this center are three interdependent narratives of a Zen Master, a monk, and an orphan boy, corresponding to the concentric graduated circles found in most mandalas. Also like the mandala, the film is unified by a multiplicity of motifs.